The house at Karamu - Fletcher, Beryl, 1938-2018 (Spinifex Press, 2003)
A funny, touching memoir of writer Beryl Fletcher's life. Beginning with a childhood in wartime New Zealand and covering a move to Australia, living in Kings Cross and later, rural New South Wales and Beryl's growing feminist consciousness.